Airborne environmental DNA metabarcoding for the monitoring of terrestrial insects—A proof of concept from the field. Issue 4 (11th March 2022) - Roger, Fabian; Ghanavi, Hamid R.; Danielsson, Natalie; Wahlberg, Niklas; Löndahl, Jakob; Pettersson, Lars B.; Andersson, Georg K. S.; Boke Olén, Niklas; Clough, Yann
Abstract: Biodiversity is in decline due to human‐induced pressures on ecosystems around the world. To be able to counteract this alarming trend, it is paramount to closely monitor biodiversity at global scales. Because this is practically impossible with traditional methods, the last decade has seen a strong push for new solutions. In aquatic ecosystems, the monitoring of species from environmental DNA (eDNA) has emerged as one of the most powerful tools at our disposal, but in terrestrial ecosystems, the power of eDNA for monitoring has so far been hampered by the local scale of the samples. In this study, we report the successful detection of insects from airborne eDNA from samples taken in the field. We compare our results to two traditional insect monitoring methods (1) light traps for moth monitoring and (2) transect walks for the monitoring of butterflies and wild bees. Airborne eDNA metabarcoding revealed DNA from six classes of arthropods, and twelve order of insects—including representatives from the four largest orders: Diptera (flies), Lepidoptera (butterflies and moths), Coleoptera (beetles), and Hymenoptera (bees, wasps, and ants). We did not detect all species observed using traditional methods and suggest further directions for the development of airborne eDNA metabarcoding. We also recovered DNA from nine species of vertebrates, including frogs, birds, and mammals as well as from 12 other phyla. Airborne eDNA has the potential to become a powerful tool for terrestrial biodiversity monitoring, with many impactful applications including the monitoring of pests, invasive, or endangered species and disease vectors.